2008
DOI: 10.3917/enf.601.0063
|View full text |Cite
|
Sign up to set email alerts
|

Les représentations d'attachement des enfants accueillis et des enfants adoptés

Abstract: Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accord préalable et écrit de l'éditeur, en dehors des cas prévus par la législation en vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
7
0
3
Order By: Relevance
“…The exception is the Eulliet et al ( 2008 ) study, which did not find any significant differences in attachment security according to age of placement. In this study of 36 foster children aged 3.6 to 5.6 years old (mean age at placement = 22.2 months, SD = 15.06), 88 % of children placed in foster care between 13 and 24 months old had secure attachments to 64 % of children placed after 25 months.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…The exception is the Eulliet et al ( 2008 ) study, which did not find any significant differences in attachment security according to age of placement. In this study of 36 foster children aged 3.6 to 5.6 years old (mean age at placement = 22.2 months, SD = 15.06), 88 % of children placed in foster care between 13 and 24 months old had secure attachments to 64 % of children placed after 25 months.…”
Section: Resultsmentioning
confidence: 84%
“…In the case of foster care children (Table 4 ), regardless of quality, all papers except one (Eulliet et al 2008 ) found that the distributions of attachment patterns are half way between institutionalised and community children when compared to control samples or general rates of attachment. The mean rate of secure attachment was 56.7 % (median = 55.5, range 45.8–69.4 %), avoidant 12.6 % (median = 8.5, range 4.2–30.6 %), ambivalent 5.58 % (median = 8.5, range 0–8.3 %) and disorganised 23.3 % (median = 28, range 0–41.7 %) (Bernier et al 2004 ; Cole 2005a , b , 2006 ; Dozier et al 2001 ; Moore and Palacio-Quintin 2001 ; Ponciano 2010 ; Smyke et al 2010 ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Ainsi, la méta-analyse de van den Dries et al (2009) met en lumière que les enfants adoptés montrent significativement moins d'attachement sécure que des enfants biologiques alors que d'autres études mettent en évidence que les enfants adoptés présentent un attachement sécure dans des proportions similaires aux enfants biologiques (Juffer & Rosenboom, 1997 ;Ponciano, 2010). Ces différences dans les résultats peuvent s'expliquer par la prise en compte, ou pas, de certains facteurs, tels que l'âge de l'enfant lors de la séparation et les changements d'environnement, pouvant influencer l'attachement de l'enfant (Euillet, Spencer, Troupel-Cremel, Fresno, & Zaouche-Gaudron, 2008).…”
Section: En Quoi Est-il Pertinent De Créer Une Intervention Renforçanunclassified